No Bull : My Life in and out of the Markets - Steinhardt, Michael (New York John wiley & sons, Inc., 2001)
"No Bull offers an account of some of the investment strategies that drove Michael Steinhardt's historic success as a hedge fund manager including a focus on his skills as an industry analyst and consummate stock picker. He also reveals how his uncanny talent for knowing when to trade against the prevailing market trend - a talent that was not always appreciated by several erstwhile high-profile clients - resulted in many of his greatest successes. Here he provides detailed accounts of some of his most sensational coups - including his momentous decision, in 1981, to stake everything on bonds - and some of his few but painful failures, such as his disastrous foray into global macro-trading in the mid-1990s."
Include Index
Keywords: United States -- Steinhardt, Michael -- Capitalists and financiers